Study of the Characteristics of Bacteria Isolated from the Pelus River, Banyumas Regency - Nurhafid, Mohammad; Indyaswari, Marthyana; Husen, Fajar; Riady, Reza Muhammad (Journal Of Artha Biological Engineering, 2023)
Community activities around the Pelus River cause pollution which affects the bacterial community found in the river. The aim of this research was to determine the characteristics of bacteria isolated from the Pelus river environment in Banyumas Regency. The method used in this research is an exploratory method where bacterial sampling is carried out at 3 different stations. The samples taken were then isolated, observed colony morphology, as well as biochemical and physiological characterization of the bacteria. The research results obtained 10 different isolates. A total of 10 isolates were obtained based on morphological differences. The characteristics of most of the Pelus River bacteria show variations ranging from enzymatic to environmental resistance which describes the waters of the Pelus River. Bacteria isolated from the water have characteristics that identify them as bacteria capable of degrading compounds